Metabolic engineering of yeasts by heterologous enzyme production for degradation of cellulose and hemicellulose from biomass: a perspective - Kricka, William; Fitzpatrick, James; Bond, Ursula (Frontiers in Microbiology, 2014)
This review focuses on current approaches to metabolic engineering of enthanologenic yeast species for the production of bioethanol from complex lignocellulose biomass sources. The experimental stratagies for the degradation of the cellulose and xylose-components of lignocellulose are reviewed. Limitations to the current approaches are discussed and novel solutions proposed.